El problema de la violencia: Conceptualización y perspectivas de análisis desde las ciencias sociales - Gonzáles Calleja, Eduardo (2006)
In the last twenty years, conflict sociology and political sociology have been the areas of social sciences that have most contributed to enrich and deepen the study of violence as a significant phenomenon of human behaviour. This has been especially the case of the findings, detailed analysis and criticisms made by the theory of rational choice, and of the debate among scientists adhering to the various currents of the collective action paradigm. Violence continues to be linked to terms like «frustration», «relative deprivation», «revolution», «crisis», «terrorism» or «collective action». Contrary to what could be expected, we are convinced that this subordination to other human sciences’ basic concepts does not hinder its theoretical elucidation at all, but rather helps to open a wide space for the necessary multidisciplinary debate on violence, in order to become in the future a sub discipline of human sciences that we could provisionally call «violentology»